DC-Based Immunotherapy Combined with Low-Dose Methotrexate Effective in the Treatment of Advanced CIA in Mice - Jun-Eui Park; Jinah Jang; Ji-Hye Choi; Mi-sun Kang; Yun-Ju Woo; Young-Rim Seong; Chan-Bum Choi; Hye-Soon Lee; Sang-Cheol Bae; Yong-Soo Bae (Journal of Immunology Research)
We have previously demonstrated that semimature dendritic cell- (smDC-) based immunotherapy is effective for the treatment of collagen-induced arthritis (CIA) prior to disease onset. In the present study, we examined the efficacy of combination therapy with smDCs and methotrexate (MTX) in advanced CIA with a score of 2-3. Combination therapy with low-dose MTX and type II collagen- (CII-) pulsed smDCs (CII-smDCs) was more effective in inhibiting disease progression than high or low-dose MTX alone or a combination of high dose MTX and CII-smDCs. The effect of CII-smDCs alone was also comparable to the combination therapy. CD4+Foxp3+ Treg populations and IL-10 secretion markedly increased, and CII-specific autoreactive T cells decreased in mice treated with CII-smDCs alone or in combination with MTX. Combination therapy reduced the secretion of interferon-γ (IFN-γ) and IL-17 with little influence on the IL-4 secretion in the mixed leukocyte reaction. These results imply that the combination therapy with low-dose MTX and smDCs is effective in controlling advanced CIA by enhancing Treg population and suppresses antigen-specific Th1/Th17 immunity, rather than initiating Th1 to Th2 immune deviation. Our findings provide a better understanding of the DC therapy in combination with MTX for the treatment of patients with rheumatoid arthritis (RA).